The First Objective Structured Practical Examination (OSPE) in Pharmacy Teaching in Poland: Designing, Implementing and Assessing the Results - Dymek, Justyna; Kowalski, Tomasz; Gołda, Anna; Polak, Wioletta; Skowron, Agnieszka (Indian Journal of Pharmaceutical Education and Research, 2020)
Background: Education of pharmacy students in preparation for their profession is still changing. It is therefore important to improve students’ skills necessary to provide pharmaceutical services according to the professional standards. One of the elements of the pharmacy curriculum is to teach and improve student’s practical and interpersonal skills e.g. solving drug problems. OSPE (Objective Structured Practical Examination) is one of a broad family of structured and objectified examinations assessing practical, clinical, communication competencies. Purposes: The aim of our study was to prepare a tool to assess the knowledge and skills of 5th-year pharmacy students in the provision of pharmaceutical care services in pharmacies and to check whether the assumed learning outcomes were achieved during studies. Methodology: OSPE was designed and implemented in accordance with the education standards for the field of pharmacy. OSPE performance scores of 5th year pharmacy students at the Faculty of Pharmacy, Jagiellonian University Medical College in Poland were analyzed using descriptive statistics. Findings: OSPE consisted of six stations of which four stations with standardized patient. Standardized patient was used in stations: pharmaceutical interview, advice for selfmedication, education about medicines, medical device education, identification and resolution of drug-related problems. OSPE was implemented in January and February 2019 and lasted 6 days. The students of the Faculty of Pharmacy were assessed in blocks of 2-2.5 hr a total of ten examiners. Conclusion: Objective Structured Practical Examinations can assess practical competence and communication skills. Appropriately designed stations make it possible to perform professional activities that reflect the real situations in pharmacy. Implementation of OSPEs may be an effective tool to assess the objective outcomes pharmacy students. Results can be used as a tool for enhancing lessons and may be considered valuable for further development OSPE.
Keywords: Objective Structured Practical Examination; Pharmacy Students; Competence; Learning outcomes; Practical skills; Assessment; Pharmacy Education